2016
DOI: 10.1159/000447531
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis after Reversal of Dabigatran by Idarucizumab: A Case Report

Abstract: We describe a 75-year-old female patient with nonvalvular atrial fibrillation who presented with acute ischemic stroke during treatment with dabigatran 2 × 110 mg per day. After informed consent, we reversed the anticoagulant effects of dabigatran using idarucizumab and applied an intravenous thrombolysis (IVT) with recombinant tissue plasminogen activator (off-label use). An intracerebral hemorrhage was excluded after systemic thrombolysis. Despite the IVT, the patient’s clinical condition deteriorated and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 5 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…2 As far as we know, there have been five case reports at the time of writing of this article, all from German centres, that have reported the successful use of idarucizumab for this indication; none had any haemorrhagic complications. 2,3 Four of these studies reported successful thrombolysis with good neurological recovery, whereas one study reported failed clinical improvement in a patient with infarcts in multiple territories. 3 Diener et al 4 have published an expert opinion on the management of these ischaemic strokes based on their experience in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As far as we know, there have been five case reports at the time of writing of this article, all from German centres, that have reported the successful use of idarucizumab for this indication; none had any haemorrhagic complications. 2,3 Four of these studies reported successful thrombolysis with good neurological recovery, whereas one study reported failed clinical improvement in a patient with infarcts in multiple territories. 3 Diener et al 4 have published an expert opinion on the management of these ischaemic strokes based on their experience in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Four of these studies reported successful thrombolysis with good neurological recovery, whereas one study reported failed clinical improvement in a patient with infarcts in multiple territories. 3 Diener et al 4 have published an expert opinion on the management of these ischaemic strokes based on their experience in Germany. They proposed that for patients who have taken dabigatran in the preceding 24 hours from the time of assessment (or 96 hours if the creatinine clearance is <30 mL/min), or for patients in whom time of last dabigatran dose is unknown and who have a prolonged APTT or TT, idarucizumab should be given if the patient is not a candidate for mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These situations introduce an additional layer of complexity given the underlying thrombotic disease states present, which was not necessarily the case with our patient. Cases where ongoing therapeutic anticoagulation with dabigatran was reversed with idarucizumab to facilitate alteplase administration have been reported . In each of these cases the patients were receiving therapeutic anticoagulation for stroke prevention in atrial fibrillation .…”
Section: Discussionmentioning
confidence: 99%
“…Idarucizumab (Praxbind), a monoclonal antibody, has been approved by the Therapeutic Good Administration (TGA) to reverse the anticoagulant activity of Dabigatran. 29 Idarucizumab specifically binds to Dabigatran, reversing its anticoagulant effect and is now approved by the TGA and available in Australia. Idarucizumab exhibited complete reversal of Dabigatran within 4hours in 89% of 123 enrolees according to an ongoing trial of patients with uncontrolled bleeding or who require urgent procedures.…”
Section: Reversal Of Doacsmentioning
confidence: 99%